Hemodialysis with Polymethylmethacrylate Restores the Response to Hepatitis B Vaccination in Chronic Dialysis Patients: Hypothesized Mechanism of Action - Ralli Chiara; Imperiali Patrizio; Gabbrilelli Claudio; Conti Paolo; Lombardi Marco; Sidoti Antonino; Capitanini Alessandro; Piluso Adriano; Tekle Kiros Seble; Duranti Diletta; Duranti Ennio (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Patients undergoing hemodialysis often present with a reduced response to anti-hepatitis B virus (anti-HBV) vaccination. The soluble form of CD40 (sCD40) is elevated in hemodialysis patients and this has been shown to correlate with lack of response to anti-HBV vaccination. Due to its high molecular weight, conventional dialyzers cannot clear sCD40. Previous studies have demonstrated, that dialysis membranes in polymethylmethacrylate (PMMA) can reduce the levels of sCD40. We have studied the effect of dialysis with PMMA membranes in patients who were non-responders to anti-HBV vaccination after  a  complete  cycle  of  vaccinations.  Interestingly,  we  found  that  significantly  more  patients  in  the PMMA group were able to mount a response to vaccination, compared to the control group (P = 0.04).